Compositional results from the Late Miocene and Pliocene of Sites U1514 and U1516: X-ray fluorescence and grain-size measurements - Gabriel Tagliaro; Hans-Jürgen Brumsack; Craig S Fulthorpe (PANGAEA, 2021)
Late Miocene and Pliocene marine sediments were cored at Sites U1514 and U1516 in the Mentelle Basin offshore Western Australia, as part of the International Ocean Discovery Program Expedition 369. Core samples were investigated to assess the chemical and physical compositional of these unconsolidated sediments, using X-Ray Fluorescence (XRF) and Grain-size analysis. XRF measurements on discrete samples (WD-XRF) were performed at the University of Oldenburg with a Panalytical AXIOS Plus spectrometer, in 63 samples from Site U1516 (Table S1) and 16 samples for Site U1514 (Table S2). Sediment sample splits were ground and homogenized in an agate ball mill. Glass beads were prepared from the sample powder after pre-oxidation with 1 g of ammonium nitrate using di-lithium tetraborate as a flux (700 mg sample, 4.2 g flux). Calibration of the XRF instrument was based on 52 international reference samples and in-house standards. Precision was determined from the pooled standard deviation of several duplicates and is better than 3% for major elements and better than 5% for trace elements when concentrations were above the detection limit. Grain-size measurements were conducted in 153 samples from Site U1516 (Table S3) using a Mastersizer 3000 laser diffraction particle analyzer at the Institute for Geophysics at the University of Texas at Austin. Dry samples were disaggregated and homogenized in water under sonic dispersion using a Hydro LV cylinder, mixing at 2800 rpm. Samples were added to the solution until obscuration values remained stable. Three measurements were performed on each sample and the median spectra were then processed.